Deepfake Parodies, Technological Spectacle, and Digital Catharsis: The Case of Iberian Son - Paz-Rebollo, María Antonia; Bonaut-Iriarte, Joseba; Vicent-Ibáñez, Mireya (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study examines 1,919 user comments on 57 deepfakes created by Iberian Son and posted on TikTok, which parody the Spanish Prime Minister, Pedro Sánchez. Content analysis and textual analysis are applied to explore whether the use of AI motivates viewing, what kind of responses they generate, and whether users infer implicit meanings not directly expressed in the videos. The results show that AI not only increases the appeal of the content but also acts as a tool for digital catharsis. The comments reveal that these videos provoke visceral reactions and reactivate latent political hate speech. In addition, they project broader ideological readings, some of which are linked to narratives typical of the far right.